Case-control study of hypertension and Parkinson’s disease - Yuen-Fann Ng (Nature Portfolio, 2021)
Abstract We evaluate the association of hypertension with PD in an Asian population and performed a meta-analysis on similar studies to address the effect of hypertension on PD risk. A matched case-control study involving 1342 Chinese subjects (671 PD and 671 age and gender-matched controls (with a mean age of 63.9 ± 9.7 and 63.5 ± 9.8 years, and identical proportion of gender distribution) was conducted. Hypertension increases PD risk by 1.9 times [OR 1.86 (1.46–2.38)]. The literature search identified 618 studies initially; however, only three matched case-control studies (all in Caucasians) met the inclusion criteria for meta-analysis. Overall analysis showed that hypertension decreases PD risk by 0.2 times [OR 0.80 (0.66–0.96)]. Hypertension increases PD risk by 1.9 times in our Asian population. However, a meta-analysis comprising of Caucasian populations showed a protective effect of hypertension suggesting that ethnic differences or other genetic or environmental factors may contribute to the divergent observation. Early diagnosis and treatment of hypertension may potentially reduce the risk of PD, at least in our population.